2020
DOI: 10.3390/f11090973
|View full text |Cite
|
Sign up to set email alerts
|

Solar Cycles in Salvage Logging: National Data from the Czech Republic Confirm Significant Correlation

Abstract: Forest ecosystems in Europe undergo cyclic fluctuations with alternating periods of forest prosperity and disturbances. Forest disturbances are caused by large-scale calamities (climate-induced and unforeseen events) resulting in an increased volume of salvage logging. In recent decades, climate change (warming, long-term droughts, more frequent storms, bark beetle outbreaks) has contributed to an increased frequency of salvage logging. However, until now, it has not been revealed what triggers national-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…Our results also showed that 15 of the 18 NPY were observed in the second half of the second part of the studied period. An increasing number of NPY during the time may be caused by an increasing number of extreme climatic events in ongoing climate change [80,86,87].…”
Section: Different Growth Conditions Of European Beech In Central Europe and The Southern Apenninesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also showed that 15 of the 18 NPY were observed in the second half of the second part of the studied period. An increasing number of NPY during the time may be caused by an increasing number of extreme climatic events in ongoing climate change [80,86,87].…”
Section: Different Growth Conditions Of European Beech In Central Europe and The Southern Apenninesmentioning
confidence: 99%
“…There is a study that describes a possible association of low sunspot activity with climatically cold periods on the Earth [32]. Solar cycles do not affect temperatures and precipitation directly, and it has been shown that solar activity is not imprinted on these factors entirely [86,96]. The total contribution of solar activity to variations in the Earth's global temperature and climate is insignificant but not negligible [97].…”
Section: Solar Cycles Climate Change and The Possible Link To European Beechmentioning
confidence: 99%
“…Finally, climate change -in particular heatwaves, long-term droughts, extreme events, secondary pests -are significant threats to forest production and stability (Rößiger et al 2019;Vacek et al 2019Vacek et al , 2020Šimůnek et al 2020;Hájek et al 2021;D'Andrea et al 2022). Pinus contorta is susceptible to the synergism of extreme temperatures combined with high precipitation variability or low precipitation during the vegetation season, primarily during May-July (Lo et al 2010;Vacek et al 2021).…”
Section: Risks Predators and Diseasesmentioning
confidence: 99%
“…This fluctuating dynamic represents a significant challenge for maintaining the resilience of these ecosystems, especially in the case of the large-scale dieback of Norway spruce (Picea abies (L.) Karst.) in Central Europe [11,12]. Therefore, the stabilization of forest ecosystems goes hand in hand with a sustainable and stable timber market and is one of the most important aims for forest management practices in future decades.…”
Section: Introductionmentioning
confidence: 99%